Chlorella vulgaris sp. microalgae as a feedstock for biofuel. (2020) - Thirugnanasambantham, R.; Elango, T.; Elangovan, K.
Abstract: As need of energy is increasing, day by day reserves of fossil fuels are exhausting and use of non-renewable fuels causes setting pollution, there's have to boost the utilization of alternation inexhaustible source of energy. Among renewable resources biodiesel is one of significant biofuel. Microalgae are well known as a promising tool for biofuel production like a renewable energy source that can be converted to biofuel. In the current study, possibility of green algae like a possible feedstock for biodiesel output continues to be evaluated. Entire 113 isolates from four samples of microalgae collected from various localities of Ramanathapuram, Tamilnadu, were screened for biodiesel production. Biomass fatty acid, yield, lipid comfortable composition as well as optimum problems for lipid production for microalgae are generic/specie unique. Chlorella vulgaris is examined as ideal applicants for biodiesel production on the foundation of biomass yield, lipid written content in addition to quality of lipids. There's should lengthen the work for mass cultivation of these microalgae on cost substrates that are low therefore price of biomass output may be lowered.